Motivasi Belajar Siswa Dalam Pembelajaran - Safitri, Anasya; Kurniawan, Krisna; Nurani, Melati Putri Dyah Ayu; Febriana, Salsabilla; S, Saridawati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the educational process at school, learning is the main activity. Learning is a conscious effort to change a person’s attitudes and behaviour. Motivation is needed to change behaviour. One type of research method based on the research location is the literature study research method. Literature study research is a series of research related to library data collection methods or research whose research objects are explored through various library information. In carrying out human activities, learning motivation is needed because it is something that can cause, channel and support human behaviour so that they are active in learning and enthusiastic to achieve optimal result. One component that encourages students to learn is motivation.